2020
DOI: 10.1038/s41598-020-59026-y
|View full text |Cite
|
Sign up to set email alerts
|

Systematic dissection of biases in whole-exome and whole-genome sequencing reveals major determinants of coding sequence coverage

Abstract: Advantages and diagnostic effectiveness of the two most widely used resequencing approaches, whole exome (WES) and whole genome (WGS) sequencing, are often debated. WES dominated largescale resequencing projects because of lower cost and easier data storage and processing. Rapid development of 3 rd generation sequencing methods and novel exome sequencing kits predicate the need for a robust statistical framework allowing informative and easy performance comparison of the emerging methods. In our study we devel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
90
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(97 citation statements)
references
References 41 publications
4
90
0
3
Order By: Relevance
“…Previous studies have suggested that the qualities of DNA sequencing with WGS and WES are similar [34], and that WES is an efficient alternative to WGS [31,35]. In support of these findings, we did not observe much difference in the median number of HQFE variants for WES and WGS in the pairwise comparison (Table 1).…”
Section: Plos Onesupporting
confidence: 89%
“…Previous studies have suggested that the qualities of DNA sequencing with WGS and WES are similar [34], and that WES is an efficient alternative to WGS [31,35]. In support of these findings, we did not observe much difference in the median number of HQFE variants for WES and WGS in the pairwise comparison (Table 1).…”
Section: Plos Onesupporting
confidence: 89%
“…These shortcomings are caused by mapping errors, which are inherent to short read sequencing approaches when applied to repetitive regions and because of the lack of targeting of regions that are outside of the exons. Because these sources of genetic variation might play a role in human disease, there is a possibility that diagnoses in PIDs are missed based on WES data [25,46]. Ultimately, it is expected in the future that WGS will offer a more complete test to assess both the coding and non-coding part of the genome, outweighing the extra costs posed by more complex analysis of the data and data storage.…”
Section: Yield Of Wes For Pid Diagnosticsmentioning
confidence: 99%
“…According to the study published by Barbitoff, Y.A. et al most of the observed bias in WES stems from mappability limitations of short reads, as well as exome probe design [29]. Due to the high complexity of the analysis, the lack of biological material, and the huge cost associated, neither WGS nor WES will be possible as routine molecular strategies used to analyze the ctDNA.…”
Section: Ctdna-the Conceptmentioning
confidence: 99%